Effect of dietary carbohydrate to lipid ratios on growth, feed conversion, protein utilisation and body composition in climbing perch, ANABAS TESTUDINEUS - M. Z. Ali; M. Zaher, M. J. Alam; M. G. Hussain (Advances in Aquaculture and Fisheries Management, 2020)
An 8-week feeding trial was conducted in a static indoor rearing system with 15 cylindrical fibre glass tanks (80 cm diameter, 75 cm deep, 70-L each) to investigate the optimum carbohydrate to lipid ratio (CHO:L ratio) in climbing perch, ANABAS TESTUDINEUS (2.15 ± 0.07 g). Five isonitrogenous (40% crude protein) and isoenergetic (17.71 kJ g-1 gross energy (GE)) fishmeal based diets with varying carbohydrate to lipid (CHO: L g/g) ratios of 0.58, 0.99, 1.53, 2.29 and 3.00 diets 1 to 5, respectively were tested. These diets had a fixed protein to energy ratio (P : E ratio) of 22.60-mg protein kJ-1 GE. They were fed to triplicate groups of 50 fish at 5% body weight per day and the feed quantity was adjusted fortnightly. Diet 1, containing 11% carbohydrate and 17% lipid with a CHO: L ratio of 0.58 produced the poorest (P<0.05) growth rate, and feed and protein efficiency. Increasing dietary carbohydrate to 24%, concomitant with a reduction in lipid content to 10.50% that resulted in a CHO: L of 2.29 significantly improved (P<0.05) growth rate, and feed and protein efficiency. But, these did not differ from diets 2, 3 and 5, containing CHO:L ratios of 0.99, 1.53 and 3.00. Apparent net protein utilization (ANPU) in fish fed diet 5 was significantly higher (P<0.05) than those receiving diets 1 and 2, but did not differ from that of diets 3 and 4. Higher lipid deposition (P<0.05) in whole body was observed with decreasing dietary CHO: L ratios and increasing lipid levels. Whole body protein of fish fed varying CHO: L diets did not show any discernible variations among the dietary treatments. This study revealed that climbing perch, ANABAS TESTUDINEUS can perform equally well on diets containing carbohydrate ranging from 14.43 to 28.81%, with 9.60 to 14.64% lipid or CHO: L g/g ratios of 0.99 to 3.00.